Elements of Entrepreneur Competencies and Intention to be Entrepreneurs - Christine Winstinindah Sandroto; Yussi Ramawati; Syarief Darmoyo (International Journal of Applied Business and International Management, 2024)
This study aims to determine the effect of the elements of entrepreneurial competencies on entrepreneurial intention in two big cities in Indonesia, namely Jakarta and Balikpapan. The population in this study are business people, both entrepreneurs and those who work in creative industries in Jakarta and Balikpapan. The number of respondents in Jakarta and Balikpapan was 305 and 162. The sampling technique used was convenience sampling. Hypothesis testing shows that the elements of achievement, personal maturity, and orientation to others partially positively and significantly influence the entrepreneurial intention of respondents in Jakarta. Meanwhile, individual achievement, thinking, and problem-solving positively and significantly influence the entrepreneurial intention of respondents in Balikpapan.